A method for continuously preparing in-mold foamed beads

The foamed beads in the mold are prepared through continuous suspension polymerization technology, which solves the problems of uneven particle size and irregular shape in the prior art, and realizes the mass production of spherical particles and the performance improvement of foam parts.

CN118952561BActive Publication Date: 2025-03-18CASHEM ADVANCED MATERIALS HI TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411450620.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-18
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing methods for preparing foamed particles in the mold lead to uneven particle size and irregular shape, resulting in uneven foaming and uneven performance of the entire plate.

Method used

The continuous suspension polymerization technology is used to prepare in-mold foamed beads, and the suspended polymerization solution completed by high-speed shearing is processed in a spiral coil, and heat treatment is performed in an oven to cure the beads.

Benefits of technology

The preparation and mass production of spherical PMI particles is realized, which solves the problems of uneven particle size and irregular shape, and improves the mechanical properties and heat resistance of foam parts.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a method for continuous preparation of in-mold foamed beads, relating to the field of polymer materials. The method includes: opening a gate to release a suspension polymerization solution, which has undergone high-speed shearing, into a storage tank; injecting the solution into the feed inlet of a spiral coil at a certain rate; and turning on a hot water heating jacket to a certain temperature. After a certain time, the beads reach the discharge sieve at the bottom of the spiral coil. Once a certain quantity is reached, the beads in the sieve are transferred to an oven for heat treatment, where they undergo in-mold foaming and solidification to obtain irregularly shaped parts. By preparing spherical PMI particles using suspension polymerization technology and applying a continuous production line to mass-produce in-mold foamed beads, the problems of poor dispersion, difficult adhesion, environmental pollution, and industrialization are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, in particular to a method for continuously preparing in-mold foaming beads. Background Art

[0002] Foam particles are a lightweight material, usually made of plastic particles that have been physically or chemically treated to form a large number of closed microporous structures inside the particles, which expands the volume and reduces the density. This material has a wide range of applications in many fields such as construction, packaging, and automobile manufacturing due to its lightweight, high strength, sound insulation, and heat preservation properties.

[0003] Patent document: A polyester foam bead and a polyester foam bead molded body and a preparation method thereof (application number: CN113416341B). The preparation method comprises the following steps: S1. The polyester foam bead raw material is granulated by an extruder to obtain polyester particles; S2. The polyester particles are immersed in a high-pressure fluid a in a water-free high-pressure container to obtain impregnated polyester particles; S3. The impregnated polyester particles are frozen and stored in an environment below 0°C to obtain frozen air-locked polyester particles; S4. The frozen air-locked polyester particles are subjected to a heating and foaming treatment.

[0004] Patent document: Polyolefin foaming composition, polyolefin foaming beads and preparation method thereof, foaming bead molded body (application number: CN114058124A) The polyolefin foaming composition comprises polyolefin and a cell nucleating agent, the cell nucleating agent is maleic anhydride styrene α methyl styrene copolymer microspheres, and the particle size of the maleic anhydride styrene α methyl styrene copolymer microspheres is 400 3900nm; based on 100 parts by weight of polyolefin, the amount of the cell nucleating agent is 0.25 10 parts by weight.

[0005] At present, the preparation method for in-mold foamed particles is generally to obtain particles by crushing the bulk polymerized foamable precursor board. Most of these particles are irregular in shape, so they cannot be called in-mold foamed beads. The particles produced by this method are uneven in size and shape, resulting in weak interface interaction between adjacent foam particles, resulting in uneven foaming of the board, uneven performance of the entire board, and local low performance.

[0006] In addition, suspension polymerization can also be used to prepare in-mold foamed beads. However, the beads prepared by the general suspension polymerization method have a small particle size and a too low yield, and cannot be produced continuously, which greatly affects its application in production. Summary of the invention

[0007] The present invention provides a method for continuously preparing in-mold foamed beads to overcome at least one technical problem in the above-mentioned background technology.

[0008] In order to achieve the above-mentioned invention object, this method proposes the following solution:

[0009] A method for continuously preparing in-mold foamed beads, characterized in that the method comprises: opening the gate of a suspension polymerization solution that has been sheared at a high speed and placing it into a storage tank, injecting the feed liquid into a spiral coil feed port at a certain rate, and turning on the hot water heating jacket to a certain temperature. After a certain period of time, the beads reach the discharge screen bucket at the bottom of the spiral coil. After reaching a certain amount, the beads in the screen bucket are transferred to an oven, and the beads are foamed and solidified in the mold after heat treatment to obtain special-shaped products.

[0010] In the above method, the preparation method of the suspension polymerization solution comprises:

[0011] S1, aqueous phase: deionized water, aqueous phase salting-out agent, and dispersion stabilizer are added to the reaction vessel in sequence, and stirred evenly at a stirring speed of 1000-2000 rpm for 0.5-1 h;

[0012] S2, oil phase: (meth) acrylic acid, (meth) acrylonitrile, initiator, copolymerizable foaming agent, and crosslinking agent are sequentially added into a reaction vessel and stirred at a stirring speed of 1000-2000 rpm for 10-30 min;

[0013] S3. Set the speed to 150-500 r / min, slowly add the oil phase into the water phase, wherein the mass ratio of oil phase to water phase is 1:4-7, mechanically stir for 30-60 min, and introduce nitrogen.

[0014] In the above method, the preparation method of the dispersion stabilizer is:

[0015] T1: nitrogen is introduced into a closed stirred reactor, and then 30-50 parts of N-vinyl pyrrolidone, 0.05-0.5 parts of lithium p-styrene sulfonate, 0.05-0.5 parts of (-)-IPC2B (allyl) borane, 500-600 parts of distilled water, and 2-5 parts of benzoyl peroxide are added, and the mixture is stirred at 70-80°C for 6-9 hours;

[0016] T2: After filtering and drying, a dispersion stabilizer of polyvinyl pyrrolidone containing lithium sulfonate and borane is obtained.

[0017] In the above method, the mass ratio of deionized water: aqueous phase salting-out agent is 100:15-20.

[0018] In the above method, the aqueous phase salting-out agent is selected from at least one of sodium chloride, sodium sulfate and ammonium sulfate.

[0019] In the above method, the mass ratio of (meth)acrylic acid: (meth)acrylonitrile: initiator: copolymerizable foaming agent: crosslinking agent: dispersant is 40-70: 40-70: 0.1-5: 1-20: 0.1-10: 0.1-3.

[0020] In the above method, the initiator is selected from at least one of benzoyl peroxide (BPO), dicumyl peroxide (DCP), azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), and azobiscyclohexylcarbonitrile (ACCN).

[0021] In the above method, the copolymerizable foaming agent is one or more of tert-butyl methacrylate, tert-butyl acrylate, and isopropyl acrylate.

[0022] In the above method, the speed is 5 mm / min, the total length of the spiral coil is 10 m and the device is placed at an angle of 15°, and the temperature of the hot water heating jacket is 50°C.

[0023] In the above method, the in-mold foaming and curing process is: fill the in-mold foaming particles into the inner cavity of the mold, heat the foaming mold according to a program, first preheat from room temperature to 160°C for 0.5 to 2 hours, then foam and cure at 120 to 240°C for 0.5 to 12 hours, the material expands and foams, fills the mold cavity, and is completely cured; cools and demolds; obtains a special-shaped product.

[0024] The reaction mechanism of the dispersion stabilizer

[0025] 1. N-vinylpyrrolidone (NVP): As a polymerization monomer, NVP provides the necessary double bonds for ring-opening polymerization. At the same time, its lactam structure brings higher polarity to the polymer chain, which is beneficial to the subsequent interaction with other components.

[0026] Lithium p-styrene sulfonate: The ionizable lithium sulfonate group is introduced to promote the dispersion of polymer chains through charge repulsion and improve stability.

[0027] (-)-IPC2B (allyl) borane: The mechanical properties and thermal stability of the final polymer are enhanced by the reaction of the borane group with the double bond of NVP.

[0028] 2. In suspension polymerization, PVP containing lithium sulfonate and borane acts as a dispersion stabilizer. This polymer not only maintains the dispersed state of the monomer droplets through the hydrophilic lithium sulfonate groups and hydrophobic skeleton in its structure, but also prevents the droplets from merging through charge repulsion. At the same time, the borane part participates in the cross-linking reaction, allowing PVP to form a more complex three-dimensional network structure, further stabilizing the entire system.

[0029] Technical effect:

[0030] 1. The spherical PMI particles are prepared by suspension polymerization, which avoids the problems of low foaming ratio, difficulty in bonding between particles, severe environmental pollution and greatly reduced foam performance after the foamable precursor sheet is crushed and foamed in the mold.

[0031] 2. The use of a continuous suspension polymerization device can be used to prepare in-mold foamed beads in batches, solving the problem that general suspension polymerization cannot be applied and industrialized. DETAILED DESCRIPTION

[0032] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0033] Detection method:

[0034] Apparent density shall comply with GB / T 6343-2009 Determination of apparent density of foam plastics and rubber;

[0035] The tensile strength is measured according to ASTM-D638-2010 Plastic Tensile Test;

[0036] The compression strength is in accordance with GB / T 8813-2008 Determination of compression properties of rigid foam plastics;

[0037] Shear strength is tested according to "ASTM-C273-2020 Shear properties of sandwich core materials";

[0038] The heat deformation temperature is determined according to "DIN 53424-1978 High temperature dimensional stability under bending and compressive stress".

[0039] Example 1

[0040] A method for continuously preparing in-mold foamed beads, characterized in that the method comprises: opening the gate of a suspension polymerization solution that has been sheared at a high speed and placing it into a storage tank, injecting the feed liquid into a spiral coil feed port at a certain rate, and turning on the hot water heating jacket to a certain temperature. After a certain period of time, the beads reach the discharge screen bucket at the bottom of the spiral coil. After reaching a certain amount, the beads in the screen bucket are transferred to an oven, and the beads are foamed and solidified in the mold after heat treatment to obtain special-shaped products.

[0041] The preparation method of the suspension polymerization solution comprises:

[0042] S1, aqueous phase: deionized water, aqueous phase salting-out agent, and dispersion stabilizer are added to the reaction vessel in sequence, and stirred evenly at a stirring speed of 1000 rpm for 0.5 h;

[0043] S2, oil phase: (meth)acrylic acid, (meth)acrylonitrile, initiator, copolymerizable foaming agent, and crosslinking agent are sequentially added into a reaction vessel and stirred at a stirring speed of 1000 rpm for 10 min;

[0044] S3. Set the speed to 150 r / min, slowly add the oil phase into the water phase, where the mass ratio of oil phase to water phase is 1:4, mechanically stir for 30 minutes, and introduce nitrogen.

[0045] The preparation method of the dispersion stabilizer is:

[0046] T1: nitrogen was introduced into a closed stirred reactor, and then 30 g of N-vinyl pyrrolidone, 0.05 g of lithium p-styrene sulfonate, 0.05 g of (-)-IPC2B (allyl) borane, 500 g of distilled water, and 2 g of benzoyl peroxide were added, and the mixture was stirred at 70°C for 6 h;

[0047] T2: After filtering and drying, a dispersion stabilizer of polyvinyl pyrrolidone containing lithium sulfonate and borane is obtained.

[0048] The mass ratio of deionized water to aqueous phase salting-out agent is 100:15.

[0049] The aqueous phase salting-out agent is sodium chloride.

[0050] The mass ratio of (meth)acrylic acid: (meth)acrylonitrile: initiator: copolymerizable foaming agent: cross-linking agent: dispersant is 60:40:0.5:8:2:1.

[0051] The initiator is selected from benzoyl peroxide (BPO).

[0052] The copolymerizable foaming agent is tert-butyl methacrylate.

[0053] The speed is 5 mm / min, the total length of the spiral coil is 10 m placed at an angle of 15°, and the temperature of the hot water heating jacket is 50°C.

[0054] The in-mold foaming and curing process is as follows: filling the in-mold foaming particles into the mold cavity, raising the temperature of the foaming mold according to a program, first preheating from room temperature to 160°C for 0.5 hour, then foaming and curing at 120°C for 0.5 hour, the material expands and foams, fills the mold cavity, and is completely cured; cooling and demolding; obtaining a special-shaped product.

[0055] The test results of this example are:

[0056] Example 1 Average particle size of beads (mm) 5.5 Density g / cm3 81 Compression strength MPa 1.23 Tensile strength MPa 1.68 Shear strength MPa 1.12 Heat deformation temperature℃ 210.4

[0057] Example 2

[0058] A method for continuously preparing in-mold foamed beads, characterized in that the method comprises: opening the gate of a suspension polymerization solution that has been sheared at a high speed and placing it into a storage tank, injecting the feed liquid into a spiral coil feed port at a certain rate, and turning on the hot water heating jacket to a certain temperature. After a certain period of time, the beads reach the discharge screen bucket at the bottom of the spiral coil. After reaching a certain amount, the beads in the screen bucket are transferred to an oven, and the beads are foamed and solidified in the mold after heat treatment to obtain special-shaped products.

[0059] The preparation method of the suspension polymerization solution comprises:

[0060] S1, aqueous phase: deionized water, aqueous phase salting-out agent, and dispersion stabilizer are added to the reaction vessel in sequence, and stirred evenly at a stirring speed of 1350 rpm for 0.5 h;

[0061] S2, oil phase: (meth) acrylic acid, (meth) acrylonitrile, initiator, copolymerizable foaming agent, and crosslinking agent are sequentially added into a reaction vessel and stirred at a stirring speed of 1350 rpm for 20 min;

[0062] S3. Set the speed to 250 r / min, slowly add the oil phase into the water phase, where the mass ratio of oil phase to water phase is 1:5, mechanically stir for 40 minutes, and introduce nitrogen.

[0063] The preparation method of the dispersion stabilizer is:

[0064] T1: nitrogen was introduced into a closed stirred reactor, and then 40 g of N-vinyl pyrrolidone, 0.2 g of lithium p-styrene sulfonate, 0.2 g of (-)-IPC2B (allyl) borane, 550 g of distilled water, and 3 g of benzoyl peroxide were added, and the mixture was stirred at 75°C for 7 h;

[0065] T2: After filtering and drying, a dispersion stabilizer of polyvinyl pyrrolidone containing lithium sulfonate and borane is obtained.

[0066] The mass ratio of deionized water to aqueous phase salting-out agent is 100:15.

[0067] The aqueous phase salting-out agent is sodium sulfate.

[0068] The mass ratio of (meth)acrylic acid: (meth)acrylonitrile: initiator: copolymerizable foaming agent: cross-linking agent: dispersant is 60:40:0.5:8:2:1.5.

[0069] The initiator is selected from dicumyl peroxide (DCP).

[0070] The copolymerizable foaming agent is tert-butyl acrylate.

[0071] The speed is 5 mm / min, the total length of the spiral coil is 10 m placed at an angle of 15°, and the temperature of the hot water heating jacket is 50°C.

[0072] The in-mold foaming and curing process is as follows: filling the in-mold foaming particles into the mold cavity, raising the temperature of the foaming mold according to a program, first preheating from room temperature to 160°C for 1 hour, then foaming and curing at 150°C for 4 hours, the material expands and foams, fills the mold cavity, and is completely cured; cooling and demolding; obtaining a special-shaped product.

[0073] The test results of this example are:

[0074] Example 2 Average particle size of beads (mm) 3.3 Density g / cm3 86 Compression strength MPa 1.42 Tensile strength MPa 1.86 Shear strength MPa 1.32 Heat deformation temperature℃ 215.7

[0075] Example 3

[0076] A method for continuously preparing in-mold foamed beads, characterized in that the method comprises: opening the gate of a suspension polymerization solution that has been sheared at a high speed and placing it into a storage tank, injecting the feed liquid into a spiral coil feed port at a certain rate, and turning on the hot water heating jacket to a certain temperature. After a certain period of time, the beads reach the discharge screen bucket at the bottom of the spiral coil. After reaching a certain amount, the beads in the screen bucket are transferred to an oven, and the beads are foamed and solidified in the mold after heat treatment to obtain special-shaped products.

[0077] The preparation method of the suspension polymerization solution comprises:

[0078] S1, aqueous phase: deionized water, aqueous phase salting-out agent, and dispersion stabilizer are added to the reaction vessel in sequence, and stirred evenly at a stirring speed of 1750 rpm for 1 h;

[0079] S2, oil phase: (meth) acrylic acid, (meth) acrylonitrile, initiator, copolymerizable foaming agent, and crosslinking agent are sequentially added into a reaction vessel and stirred at a stirring speed of 1750 rpm for 20 min;

[0080] S3. Set the speed to 350 r / min, slowly add the oil phase into the water phase, where the mass ratio of oil phase to water phase is 1:6, mechanically stir for 50 minutes, and introduce nitrogen.

[0081] The preparation method of the dispersion stabilizer is:

[0082] T1: nitrogen was introduced into a closed stirred reactor, and then 40 g of N-vinyl pyrrolidone, 0.4 g of lithium p-styrene sulfonate, 0.4 g of (-)-IPC2B (allyl) borane, 550 g of distilled water, and 4 g of benzoyl peroxide were added, and the mixture was stirred at 75°C for 8 h;

[0083] T2: After filtering and drying, a dispersion stabilizer of polyvinyl pyrrolidone containing lithium sulfonate and borane is obtained.

[0084] The mass ratio of deionized water to aqueous phase salting-out agent is 100:20.

[0085] The aqueous phase salting-out agent is sodium chloride.

[0086] The mass ratio of (meth)acrylic acid: (meth)acrylonitrile: initiator: copolymerizable foaming agent: cross-linking agent: dispersant is 60:40:0.5:8:2:2.

[0087] The initiator is selected from azobisisobutyronitrile (AIBN).

[0088] The copolymerizable foaming agent is tert-butyl acrylate.

[0089] The speed is 5 mm / min, the total length of the spiral coil is 10 m placed at an angle of 15°, and the temperature of the hot water heating jacket is 50°C.

[0090] The in-mold foaming and curing process is as follows: filling the in-mold foaming particles into the mold cavity, raising the temperature of the foaming mold according to a program, first preheating from room temperature to 160°C for 1.5 hours, then foaming and curing at 200°C for 8 hours, the material expands and foams, fills the mold cavity, and is completely cured; cooling and demolding; obtaining a special-shaped product.

[0091] The test results of this example are:

[0092] Example 3 Average particle size of beads (mm) 2.2 Density g / cm3 84 Compression strength MPa 1.57 Tensile strength MPa 2.04 Shear strength MPa 1.43 Heat deformation temperature℃ 213.4

[0093] Example 4

[0094] A method for continuously preparing in-mold foamed beads, characterized in that the method comprises: opening the gate of a suspension polymerization solution that has been sheared at a high speed and placing it into a storage tank, injecting the feed liquid into a spiral coil feed port at a certain rate, and turning on the hot water heating jacket to a certain temperature. After a certain period of time, the beads reach the discharge screen bucket at the bottom of the spiral coil. After reaching a certain amount, the beads in the screen bucket are transferred to an oven, and the beads are foamed and solidified in the mold after heat treatment to obtain special-shaped products.

[0095] The preparation method of the suspension polymerization solution comprises:

[0096] S1, aqueous phase: deionized water, aqueous phase salting-out agent, and dispersion stabilizer are sequentially added into the reaction vessel and stirred evenly at a stirring speed of 2000 rpm for 1 h;

[0097] S2, oil phase: (meth)acrylic acid, (meth)acrylonitrile, initiator, copolymerizable foaming agent, and crosslinking agent are sequentially added into a reaction vessel and stirred at a stirring speed of 2000 rpm for 30 min;

[0098] S3, set the speed to 500r / min, slowly add the oil phase into the water phase, wherein the mass ratio of oil phase to water phase is 1:7, mechanically stir for 60min, and introduce nitrogen.

[0099] The preparation method of the dispersion stabilizer is:

[0100] T1: nitrogen was introduced into a closed stirred reactor, and then 50 g of N-vinyl pyrrolidone, 0.5 g of lithium p-styrene sulfonate, 0.5 g of (-)-IPC2B (allyl) borane, 600 g of distilled water, and 5 g of benzoyl peroxide were added, and the mixture was stirred at 80°C for 9 h;

[0101] T2: After filtering and drying, a dispersion stabilizer of polyvinyl pyrrolidone containing lithium sulfonate and borane is obtained.

[0102] The mass ratio of deionized water to aqueous phase salting-out agent is 100:20.

[0103] The aqueous phase salting-out agent is ammonium sulfate.

[0104] The mass ratio of (meth)acrylic acid: (meth)acrylonitrile: initiator: copolymerizable foaming agent: cross-linking agent: dispersant is 60:40:0.5:8:2:2.8.

[0105] The initiator is selected from azobisisoheptanonitrile (ABVN).

[0106] The copolymerizable foaming agent is isopropyl acrylate.

[0107] The speed is 5 mm / min, the total length of the spiral coil is 10 m placed at an angle of 15°, and the temperature of the hot water heating jacket is 50°C.

[0108] The in-mold foaming and curing process is as follows: filling the in-mold foaming particles into the mold cavity, raising the temperature of the foaming mold according to a program, first preheating from room temperature to 160°C for 2 hours, then foaming and curing at 240°C for 12 hours, the material expands and foams, fills the mold cavity, and is completely cured; cooling and demolding; obtaining a special-shaped product.

[0109] The test results of this example are:

[0110] Example 4 Average particle size of beads (mm) 0.8 Density g / cm3 82 Compression strength MPa 1.33 Tensile strength MPa 1.84 Shear strength MPa 1.29 Heat deformation temperature℃ 208.5

[0111] Comparative Example 1

[0112] This example is the same as Example 3 except that no dispersion stabilizer is added.

[0113] The test results of this example are:

[0114] Comparative Example 1 Average particle size of beads (mm) Unable to form regular spherical beads Density g / cm3 83 Compression strength MPa 1.01 Tensile strength MPa 1.22 Shear strength MPa 0.97 Heat deformation temperature℃ 193.2

[0115] Comparative Example 2

[0116] This example is the same as Example 3 except that lithium p-styrene sulfonate is not added when preparing the dispersion stabilizer.

[0117] The test results of this example are:

[0118] Comparative Example 2 Average particle size of beads (mm) Unable to form regular spherical beads Density g / cm3 87 Compression strength MPa 1.16 Tensile strength MPa 1.37 Shear strength MPa 1.04 Heat deformation temperature℃ 204.8

[0119] Comparative Example 3

[0120] This example is the same as Example 1 except that (-)-IPC2B (allyl) borane is not added when preparing the dispersion stabilizer.

[0121] The test results of this example are:

[0122] Comparative Example 3 Average particle size of beads (mm) 2.5 Density g / cm3 81 Compression strength MPa 1.13 Tensile strength MPa 1.48 Shear strength MPa 1.08 Heat deformation temperature℃ 194.6

[0123] As can be seen from the above specific implementation scheme, the present invention prepares spherical PMI particles through suspension polymerization technology and uses a continuous device to mass-produce in-mold foaming beads, which effectively solves the industrialization problem of PMI beads. In addition, PVP containing lithium sulfonate and borane is used as a dispersion stabilizer to improve the mechanical properties and heat resistance of the foamed parts.

[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, and these simple modifications all belong to the protection scope of the present invention. In addition, the various embodiments of the present invention can also be arbitrarily combined, as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for continuously preparing in-mold foamed beads, characterized in that: The continuous preparation method of in-mold foamed beads comprises: opening the gate of a suspension polymerization solution that has been sheared at a high speed and placing it into a storage tank, injecting the liquid into a feeding port of a spiral coil at a certain rate, and turning on a hot water heating jacket to a certain temperature. After a certain period of time, the beads reach the discharge screen bucket at the bottom of the spiral coil. After a certain amount of beads reaches a certain amount, the beads in the screen bucket are transferred to an oven, and the beads are foamed and solidified in the mold after heat treatment to obtain a special-shaped product; The preparation method of the suspension polymerization solution comprises: S1, aqueous phase: deionized water, aqueous phase salting-out agent, and dispersion stabilizer are added to the reaction vessel in sequence, and stirred evenly at a stirring speed of 1000-2000 rpm for 0.5-1 h; S2, oil phase: (meth) acrylic acid, (meth) acrylonitrile, initiator, copolymerizable foaming agent, and crosslinking agent are sequentially added into a reaction vessel and stirred at a stirring speed of 1000-2000 rpm for 10-30 min; S3, set the speed to 150-500r / min, slowly add the oil phase into the water phase, wherein the mass ratio of oil phase to water phase is 1:4-7, mechanically stir for 30-60min, and introduce nitrogen; The preparation method of the dispersion stabilizer is: T1: nitrogen is introduced into a closed stirred reactor, and then 30-50 parts of N-vinyl pyrrolidone, 0.05-0.5 parts of lithium p-styrene sulfonate, 0.05-0.5 parts of (-)-IPC2B (allyl) borane, 500-600 parts of distilled water, and 2-5 parts of benzoyl peroxide are added, and the mixture is stirred at 70-80°C for 6-9 hours; T2: After filtering and drying, a dispersion stabilizer of polyvinyl pyrrolidone containing lithium sulfonate and borane is obtained.

2. A method for continuously preparing in-mold foamed beads according to claim 1, characterized in that: The mass ratio of the deionized water to the aqueous phase salting-out agent is 100:15-20, and the aqueous phase salting-out agent is selected from at least one of sodium chloride, sodium sulfate, and ammonium sulfate.

3. The method for continuously preparing in-mold foamed beads according to claim 1, characterized in that: The mass ratio of (meth)acrylic acid: (meth)acrylonitrile: initiator: copolymerizable foaming agent: cross-linking agent: dispersant is 40-70: 40-70: 0.1-5: 1-20: 0.1-10: 0.1-3.

4. The method for continuously preparing in-mold foamed beads according to claim 1, characterized in that: The initiator is selected from at least one of benzoyl peroxide (BPO), dicumyl peroxide (DCP), azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), and azobiscyclohexylcarbonitrile (ACCN).

5. The method for continuously preparing in-mold foamed beads according to claim 1, characterized in that: The copolymerizable foaming agent is one or more of tert-butyl methacrylate, tert-butyl acrylate and isopropyl acrylate.

6. The method for continuously preparing in-mold foamed beads according to claim 1, characterized in that: The speed is 5 mm / min, the total length of the spiral coil is 10 m placed at an angle of 15°, and the temperature of the hot water heating jacket is 50°C.

7. The method for continuously preparing in-mold foamed beads according to claim 1, characterized in that: The in-mold foaming and curing process is as follows: filling the in-mold foaming particles into the inner cavity of the mold, raising the temperature of the foaming mold according to a program, first preheating from room temperature to 160°C for 0.5 to 2 hours, then foaming and curing at 120 to 240°C for 0.5 to 12 hours, the material expands and foams, fills the mold cavity, and is completely cured; cooling and demolding; obtaining a special-shaped product.

Citation Information

Patent Citations

  • A polyester foamed bead and a molded polyester foamed bead body thereof and a method for preparing the same.

    CN113416341B

  • Polyolefin foaming composition, polyolefin foaming bead, preparation method of polyolefin foaming bead, and foaming bead formed body

    CN114058124A

  • Method for producing modified conjugated diene polymer, polymer composition, crosslinked polymer and tire

    CN104662046A

  • Physical phase-split dynamic polymer and application thereof

    CN108342049A